Sosialisasi Pentingnya Urban Farming sebagai Ketahanan Pangan Keluarga pada Era New Normal - Priarti Megawanti; Erna Megawati; Maman Paturahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
At the end of 2019, the world was shocked by the emergence of the Covid-19 outbreak, which on May 17, 2020, totaled 4,719,812 cases with 312,215 people dead and 1,811,611 patients who have recovered, and every day the number of victims continues to grow. Within a few months since it was discovered, the Covid-19 virus, which stood for Coronavirus Disease and was discovered in 2019, has made the world experience many changes from various sectors. Almost all people in the world feel the fear of this plague. Posyandu Melati is an Integrated Service Post located in the Sawangan area, Depok. The health workers from the local Puskesmas (Community Health Center) usually carry out routine activities related to the health and empowerment of the surrounding community. During the Covid 19 pandemic, many routine agendas had to be postponed or canceled due to the PSBB (Large-Scale Social Restriction) policy. Posyandu cadres and health workers still want to help the community and carry out positive activities to help people in this pandemic era. To spark their desire to initiate local communities in carrying out urban farming activities, it is necessary to conduct socialization about urban farming. Urban farming, in general, is better known as vegetable farming in the yard, which can be done hydroponically or with soil. They need information about the benefits of urban farming to help people maintain food security for their families by growing their food crops in their home yards.